Reinventing the wheel: The incidence and cost implication of duplication of effort in patient education materials development. Issue 6 (June 2021) - Papadakos, Janet; Giannopoulos, Eleni; Forbes, Leta; Fox, Colleen; Jain, Priyanka; McBain, Sarah; Mittman, Nicole; Moody, Lesley; Samoil, Diana; McLeod, Robin
Highlights: The development of patient education materials is costly and resource-intensive and there is no formal process for sharing materials. More than half of the materials had duplicate content (n = 166, 55%), a small number were adapted (n = 27, 9%), and (n = 111, 37%) were unique. The opportunity for cost savings if duplication was avoided is ∼$800, 000.00 for systemic therapy materials produced in cancer centres alone. The majority of materials are amenable to adaptation meaning that the content was not dependent on a specific institutional context (n = 283, 93%). Abstract: Objective: The development of patient education (PE) materials is costly and resource-intensive, and no mechanisms exist for sharing materials across cancer centers/hospitals to limit duplicated effort. The aim of this study was to explore the incidence and cost implication of duplicated PE efforts. Methods: PE leaders from all (14) cancer centers in Ontario, Canada, submitted their collections of systemic therapy PE materials. Materials were categorized by topic and were coded as duplicate (more than one other material exists on the same topic and there was significant content and/or textual overlap), adapted (material was adapted from an existing material) or unique (no other material addresses the topic). Results: 304 materials were included and <50 % of materials had duplicate content (n = 166, 55 %), a small proportion were adapted (n = 27, 9%), and less than half were unique (n = 111, 37 %). The majority of materials were considered amenable to adaptation meaning that the content was not dependent on a specific institutional context (n = 283, 93 %). The opportunity for cost savings if duplication of effort could be avoided is approximately $800 K for systemic therapy materials produced in cancer centers. Conclusion: There is need to refine the process for developing PE materials. Creating mechanisms of sharing can help facilitate equal access to materials and can result in significant cost savings. Practice Implications: Efforts are needed to better coordinate the development of PE materials among patient educators. Better coordination would allow patient education programs to focus on other important challenges.